The Localization of Transfer RNA(5)(Lys) Genes in Drosophila melanogaster - Grigliatti, T. A. (1974)
Transfer RNA(5)(Lys) was isolated and purified from Drosophila melanogaster. It was iodinated in vitro with sodium [(125)I]iodide and hybridized in situ to the polytene salivary gland chromosomes from Drosophila. Autoradiographs exposed three to four weeks allowed the localization of this tRNA to the right arm of chromosome 2 between bands 48F and 49A.